Unsuccessful trial accrual and human subjects protections: An empirical analysis of recently closed trials - Carlisle, Benjamin; Kimmelman, Jonathan; Ramsay, Tim; MacKinnon, Nathalie (Clinical trials (London, England), 2015)
Background Ethical evaluation of risk–benefit in clinical trials is premised on the achievability of resolving research questions motivating an investigation. Objective To determine the fraction and number of patients enrolled in trials that were at risk of not meaningfully addressing their primary research objective due to unsuccessful patient accrual. Methods We used the National Library of Medicine clinical trial registry to capture all initiated phases 2 and 3 intervention clinical trials that were registered as closed in 2011. We then determined the number that had been terminated due to unsuccessful accrual and the number that had closed after less than 85% of the target number of human subjects had been enrolled. Five factors were tested for association with unsuccessful accrual. Results Of 2579 eligible trials, 481 (19%) either terminated for failed accrual or completed with less than 85% expected enrolment, seriously compromising their statistical power. Factors associated with unsuccessful accrual included greater number of eligibility criteria (p = 0.013), non-industry funding (25% vs 16%, p < 0.0001), earlier trial phase (23% vs 16%, p < 0.0001), fewer number of research sites at trial completion (p < 0.0001) and at registration (p < 0.0001), and an active (non-placebo) comparator (23% vs 16%, p < 0.001). Conclusion A total of 48,027 patients had enrolled in trials closed in 2011 who were unable to answer the primary research question meaningfully. Ethics bodies, investigators, and data monitoring committees should carefully scrutinize trial design, recruitment plans, and feasibility of achieving accrual targets when designing and reviewing trials, monitor accrual once initiated, and take corrective action when accrual is lagging.